Opening the Cage: Stories of Church and Gender, Margaret Ann Franklin and Ruth Sturmey Jones, eds. ... - Mahood, Louise H. (Canadian Woman Studies/les cahiers de la femme, 1989)
Sisters in Spirit: Mormon Women in Historical and Cultural Perspective, Maureen Ursenbach Beecher and Lavina Fielding Anderson, eds.; Clergy Women and Their Worldviews, Martha Long Ice